MEETINGS BETWEEN BODIES IN CONTINUING TRAINING IN YOGA: THE TEACHING BEING AND THE TEACHING COLLECTIVE - Rossi, Fernanda [UNESP]; Ehrenberg, Monica Caldas (Univ Estadual Sudoeste Bahia, 2022)
The article analyzes teachers' conceptions and collective constructions in teaching, driven by corporeality and bodily experiences in a continuing education program, with the participation of 45 teachers in the areas of Physical Education, Pedagogy, Art and Special Education, of a Municipal System of Education in the interior of Sao Paulo. The research is based on qualitative assumptions and data generated by a focus group and questionnaire. It was concluded that the bodily experiences in the continuing education potentiated reflections and attitudes in relation to being and being a teacher imbricated in the same existence, implying new attitudes and openness to the understanding of the teaching function. And by sharing and engendering experiences and knowledge collectively, ties were strengthened and relationships were strengthened to rethink teaching.
Keywords: continuing education of teachers; body; bodily experiences; yoga